2014
DOI: 10.1007/s00192-014-2352-7
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing TVT-O and TVT-S for the treatment of stress urinary incontinence: 2-year results

Abstract: The efficacy of the TVT-S was similar to that of the TVT-O after 2 years' assessment. This cohort will continue to be followed in order to maintain commitment to contributing data on long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Regarding the differences with other studies reporting a significant lower medium-term efficacy of TVT-Secur [10,[17][18][19][20], it must be said that also short-term follow-up showed unsatisfying results, while randomized trial reporting favorable outcomes in the short-term confirmed these results on the medium-term [6,7,9,13]. Thus, it can be hypothesized that two kind of recurrences exist for TVT-Secur: short-term failures, mainly linked to an incorrect positioning or early failure of the sling and identified both at short-and long-term, and long-term recurrences, probably due to insufficiency of the tape in avoiding SUI.…”
Section: Commentmentioning
confidence: 72%
See 1 more Smart Citation
“…Regarding the differences with other studies reporting a significant lower medium-term efficacy of TVT-Secur [10,[17][18][19][20], it must be said that also short-term follow-up showed unsatisfying results, while randomized trial reporting favorable outcomes in the short-term confirmed these results on the medium-term [6,7,9,13]. Thus, it can be hypothesized that two kind of recurrences exist for TVT-Secur: short-term failures, mainly linked to an incorrect positioning or early failure of the sling and identified both at short-and long-term, and long-term recurrences, probably due to insufficiency of the tape in avoiding SUI.…”
Section: Commentmentioning
confidence: 72%
“…Even though a number of randomized studies report on midterm efficacy of TVT-Secur, some reporting good outcomes [6][7][8][9], other indicating a high failure rate [10,[18][19][20], to our knowledge this is the first to report a 5 year follow-up. Meta-analysis of studies evaluating short and medium-term efficacy of TVT-Secur show a lower efficacy of this single-incision sling in comparison with traditional MUS [4,5].…”
Section: Commentmentioning
confidence: 81%
“…Among them, midurethral slings are the most frequently used and their estimated success rate is about 80-90 % [3]. However, the National Institute for Health and Care Excellence (NICE) and the American College of Obstetricians and Gynecologists (ACOG) guidelines suggest that periurethral bulking agents should be considered as one of several treatment options for patients with significantly decreased urethral mobility and patients who have failed conservative therapy [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to comment on the role of Ethicon in sponsoring RCTs, because the published reports seldom mention funding sources. Only four of the RCTs identified in this review were registered in ClinicalTrials.gov: of those, Gynecare was mentioned as a collaborator for only one [91,96].…”
Section: Stage 3 -Public Acceptance and Third-party Endorsement No Pmentioning
confidence: 99%
“…Stage 5 -RCTs, n =19 [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Nineteen papers described results from 15 RCTs (Appendix A). These more rigorous studies started to appear in 2010, although the RCTs were small (the largest study recruited 285 subjects [85]).…”
Section: Stage 3 -Public Acceptance and Third-party Endorsement No Pmentioning
confidence: 99%